Integrating Padlet In Arabic Language Learning To Improve Students' Speaking Skills at UniSZA - Nor Zahidah Ahmad; Ruhiyah Sakinah Kayati; Hazrati Yahaya; Ibrahim Youssef Abdelhamid; Ragab Ragab Ibrahim Ahmed Awad (Ijaz Arabi Journal of Arabic Learning, 2026)
This study aims to assess the proficiency level of Arabic speaking skills among students of the Faculty of Contemporary Islamic Studies at Universiti Sultan Zainal Abidin (UniSZA) who are enrolled in Arabic language courses as core faculty subjects. This study is important as the findings will enable Arabic language instructors to identify weaknesses and factors influencing students' achievements, thereby improving teaching and learning techniques in the classroom. The study was conducted with 80 first-year bachelor’s degree students in Islamic Studies at the Faculty of Contemporary Islamic Studies, currently taking the Maharah al-Istima’ wa al-Kalam course at the Gong Badak campus. This study adopts a descriptive qualitative approach. The collected data will be analyzed using content analysis and descriptive analysis methods. Triangulation methods comprising of methodology, time, and sources are also utilized for data verification, including videos of group activities by the students. In conclusion, this study aims to identify students’ ability in acquiring foreign language, especially speaking skills through interactive e-learning language activities. This study will also suggest effective learning and teaching strategies and approaches for mastering the Arabic language, particularly speaking skills, among non-native speakers.